The impacts of environmental and climate targets on agriculture: Policy options in Italy - Cortignani, R. (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2022)
This study is aimed at proposing a model to assess the economic private costs for farms deriving from the implementation of some of the environmental targets set by the European Farm to Fork strategy and the objective of a carbon-neutral agricultural sector, by also evaluating the synergies and trade-offs between environmental objectives. An agro-economic supply model, based on mathematical programming and microdata from the Farm Accountancy Data Network, is used. The model is applied to Italian agriculture as a case study. Results show losses in added value, higher level of resource efficiency and synergies among different targets. Policy implications include exploiting the synergies and accompanying the transition with measures aimed at compensating the most impacted sectors.